Energy consumtion and enviromental effects of passenger transport modes - a life cycle study on passenger transport modes - Kalenoja, Hanna (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
Energy consumption and environmental effects of different passenger transport modes vary on the different stages of the fuel chain and during the production and maintenance of vehicles and infrastructure. Energy consumption and the environmental effects calculated per passenger mileage depend strongly on the vehicle occupancy. The properties of transport modes on urban areas and on the long distance transport have been evaluated in this study. The energy consumption and environmental effects calculated per passenger mileage have been assessed for passenger car, bus, tram, train, aeroplane and ferry. The emissions have been evaluated during the whole fuel chain. In this stud y only the airborne emissions have been taken into account. In the energy consumption calculations the energy content of vehicles and the infrastructure, the energy consumption during the fuel chain and during the end use have been taken into consideration.